Growth response of Spirulina platensis in papaya skin extract and antimicrobial activities of Spirulina extracts in different culture media (Bangladesh Journal of Scientific and Industrial Research, 2012)
Growth response of Spirulina platensis in papaya skin extract media and their antimicrobial activity were studied. Five different concentrations  e.g. 10gm/L, 8gm/L, 6 gm/L, 4 gm/L and 2gm/L of Papaya (Carica papaya) skin extract media and BD1 (control) medium were used  in this study. After 8 days of cultivation, the optical density (0.33) was recorded in BD1 medium and among the five different concentrations  of papaya skin extract media the maximum was found (0.31) in 6gm/L. Antimicrobial activity of Spirulina platensis grown in three  media namely Zarrouk, BD1 media and media made from papaya skin extract was also studied. Only freeze dried Spirulina platensis powder  extract showed inhibitory effect against bacteria and no antifungal activity was observed. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11445 Bangladesh J. Sci. Ind. Res. 47(2), 147-152, 2012